Carotenoid accumulation in the eyespot apparatus required for phototaxis is independent of chloroplast development in Euglena gracilis. (September 2020) - Tamaki, Shun; Tanno, Yuri; Kato, Shota; Ozasa, Kazunari; Wakazaki, Mayumi; Sato, Mayuko; Toyooka, Kiminori; Maoka, Takashi; Ishikawa, Takahiro; Maeda, Mizuo; Shinomura, Tomoko
Graphical abstract: Highlights: Eyespot of E. gracilis is formed independently of chloroplast development. Carotenoids are synthesized independently of chloroplast development in E. gracilis . Eyespot acts during negative phototaxis independently of chloroplast development. Abstract: Euglena gracilis exhibits photomovements in response to various light stimuli, such as phototactic and photophobic responses. Our recent study revealed that carotenoids in the eyespot apparatus are required for triggering phototaxis in this alga. However, the role of chloroplasts in eyespot formation is not understood. Here, we isolated carotenoid-less ( cl ) strains of E. gracilis from cells silenced gene expression of phytoene synthase ( EgcrtB ). Unlike WT, the culture colors of cl1, cl3, and the non-photosynthetic mutant SM-ZK were orange, while that of cl4 was white. Electron microscope observations showed that SM-ZK, cl1, and cl3 had no developed chloroplast and formed a normal eyespot apparatus, similar to that of WT, but this was not the case for cl4 . Carotenoids detected in WT were diadinoxanthin, neoxanthin, and β-carotene. However, the most abundant species of SM-ZK, cl1, and cl3 was zeaxanthin, and there was no diadinoxanthin or neoxanthin. Photomovement analysis showed that SM-ZK, cl1, and cl3 exhibited negative phototactic and photophobic responses, similar to those of WT, whereas cl4 lacked negative phototaxis. Taken together, the formation of the eyespot apparatus required for phototaxis is independent of chloroplast development in E. gracilis, suggesting that this property is different from other photosynthetic flagellates.